(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
In this article, the authors present a reflection on the creation process of the theatrical video Amantes em confinamento, particularly regarding the text, acting and sound design. The work was carried out remotely, between September 2020 and January 2021, within the scope of the university extension of the Universidade Federal de Sergipe. The construction was collaborative and included teachers and students from the Theater and Film and Audiovisual courses. The video call was taken as a scenic device and not only as a tool for communication, rehearsals and image capture. The work showed us that it is possible to collaboratively create, rehearse and act by remote means, and it motivated us to continue investigating this format.